Retrospective evaluation of toceranib phosphate (Palladia®) use in the treatment of gastrointestinal stromal tumors of dogs. (11th October 2018) - Berger, Erika P.; Johannes, Chad M.; Jergens, Albert E.; Allenspach, Karin; Powers, Barbara E.; Du, Yingzhou; Mochel, Jonathan P.; Fox, Leslie E.; Musser, Margaret L.
Abstract : Background: Gastrointestinal stromal tumors (GISTs) are uncommon intestinal neoplasms in the dog. Literature regarding adjunctive therapy for GISTs in dogs is sparse. High‐risk GISTs in humans respond to tyrosine kinase inhibition in the adjuvant setting. Objectives: To review cases of toceranib phosphate use in dogs with GISTs and provide initial assessment of possible biological activity. A secondary aim was to evaluate patient and tumor characteristics for possible prognostic value. Animals: Twenty‐seven dogs with confirmed GISTs based on histopathology and immunohistochemistry treated with toceranib. Methods: Retrospective study in which cases of toceranib use in dogs with GIST were solicited using the American College of Veterinary Internal Medicine Oncology and Small Animal Internal Medicine listservs. Results: Five of 7 dogs with gross disease experienced clinical benefit (71%; 3 complete responses, 1 partial response, 1 stable disease). These included 2 dogs with durable responses after toceranib discontinuation. Median progression‐free interval (PFI) in dogs with gross disease was 110 weeks (range, 36‐155 weeks). Median PFI in dogs with microscopic disease was 67 weeks (range, 9‐257 weeks). Metastasis at diagnosis ( P = 0.04) and high mitotic index ( P < 0.001) were associated with shorter PFI in toceranib‐treated dogs. Conclusions and Clinical Importance: Biological activity of toceranib is evident in dogs with gross disease. Metastasis of GIST at diagnosis, as well as high tumor mitotic index, was associated with shorter PFI in toceranib‐treated dogs. Larger studies are needed to define postsurgical risk and refine the use of toceranib in dogs with gross and microscopic GIST.